Bermain bagi anak, bukan sekedar bermain - Muhammad Idrus (EL-TARBAWI, 2002)
Playing for childreen is not only playing something like adult seen. But also   exploring his or her surround, knowing each others. Playing for children could he a good time for parent to transform a good value. Refer to what Rasulullah said, "if you have child you must be child (but not be childish) It means, we must be playing together with our children, make them happy. Today, we see many parents want their children to take a short course like English Course, dance, model, singing etc. if we ask them, what purpose all of their children's activity. They make rationalization that all of their children's activity is for their children's future, it is rights or it's just a ticket for parent to get into one community. It is coercion to child. We must give our children time for playing, whatever he or she does. It is better for them than force them to take a course, while he or she does not need it.Key word: Playing, Child rearing